THE EFFECT OF PRICING STRATEGY AND SERVICE QUALITY ON PURCHASE DECISIONS AT ALDI MOTOR AUTOSERVICE - Sanida, Nuris; Kurniawan, Indra (Distribusi - Journal of Management and Business, 2026)
The purpose of this study is to determine the effect of pricing strategy and service quality on purchasing decisions at Aldi Autoservice Motorcycle Workshop. The population in this study consisted of all consumers who made transactions at Aldi Motor Autoservice Workshop in 2024, totaling 3,135 customers. The sample used in this study consisted of 97 respondents. This research used a quantitative research method. Based on quantitative analysis using a statistical approach, the multiple linear regression equation obtained was Y = 1.173 + 0.043X1 + 0.916X2 + e. The results of the t-test show that the pricing strategy variable has no effect and is not significant on purchasing decisions at Aldi Motor Autoservice Workshop. Meanwhile, the service quality variable has a significant effect on purchasing decisions at Aldi Motor Autoservice Workshop. Simultaneously, pricing strategy and service quality have a significant effect on purchasing decisions at Aldi Motor Autoservice Workshop. Based on the coefficient of determination analysis, pricing strategy and service quality influence purchasing decisions by 85.5%.